"Characteristically Generous"? Australian Responses to Refugees Prior to 1951. (June 2014) - Stats, Katrina
<x xml:space="preserve">Abstract</x> When Australia pledged to accept 15, 000 Jewish refugees from Europe in 1938, it was applauded by the London Times as "a characteristically generous contribution" and an example for others. Australia's reputation for generous humanitarianism was solidified after the war when it absorbed more than 180, 000 of Europe's Displaced Persons and committed to international human rights instruments designed to protect refugees and asylum seekers. This reputation has been used to both defend and critique the nation's contemporary responses to asylum seekers. Recent Australian Prime Ministers have invoked Australia's proud record of refugee resettlement to deflect criticism of their tough border control policies, policies which critics charge repudiate the nation's humanitarian traditions. This article critically reviews the history of Australia's responses to refugees and asylum seekers prior to 1951 and demonstrates that contemporary border control policies are neither a deviation from, nor defence of, a proud humanitarian record. Rather, they embody the migration management approach to refugees that provided impetus for Federation in 1901, governed Australia's response to the Jewish refugee crisis in the 1930s, and shaped its conditional acceptance of the Displaced Persons and the position it adopted in the drafting of the United Nations Convention Relating to the Status of Refugees in 1951.